Mercy Watson : princess in disguise - DiCamillo, Kate (DiCamillo, Kate. Mercy Watson collection ;, 2007)
Persuaded by the word "treating" to dress up as a princess for Halloween, Mercy the pig's trick-or-treat outing has some very unexpected results.